The hard facts of the Grimms' fairy tales - Tatar, Maria, 1945- (Princeton classics, 2019)
Murder, mutilation, cannibalism, infanticide, and incest: the darker side of classic fairy tales is the subject of this groundbreaking and intriguing study of Jacob and Wilhelm Grimm's Nursery and Household Tales. This expanded edition includes a new preface and an appendix featuring translations of six tales with commentary by Maria Tatar. Throughout the book, Tatar draws on the disciplinary tools of psychoanalysis and folklore while also providing historical context to explore the harsher aspects of these stories, presenting new interpretations of tales that engage in a kind of cultural repetition compulsion. No other book so thoroughly challenges us to rethink the happily-ever-after of these classic stories.